Effect of digestive ripening agent on nanoparticle size in the digestive ripening process - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Chemical Physics Letters, 2012)
Digestive ripening is an efficient method that leads to monodispersed nanoparticles from polydispersed ones. A systematic investigation of digestive ripening with different agents viz. dodecanethiol and dodecylamine on different metallic systems is presented. It is shown that both the metallic system involved and the digestive ripening agent have influences on the final size distribution. Further, it is demonstrated that the interaction strength between the different metals and the digestive ripening agents based on Hard Soft Acid Base principles could be invoked to explain the variation in nanoparticle size. (C) 2012 Elsevier B.V. All rights reserved.

Fine control of nanoparticle sizes and size distributions: temperature and ligand effects on the digestive ripening process - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Nanoscale, 2013)
It is demonstrated that a fine control over the size and size distribution of nanoparticles could be achieved using digestive ripening at different temperatures. Such variations in size and size distributions hugely influence the self-assembled processes in nanoparticles, and result in superlattice structures that are controlled by subtle interplay between ligand orientational entropy and their interdigitation and the van der Waals attraction between the metal cores.

Dilution does the trick: role of mixed solvent evaporation in controlling nanoparticle self-assembly - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
An easy and convenient way to prepare superlattices of amine capped gold nanoparticles is presented. It is clearly established that solvent evaporation significantly influences the nature of resulting superlattices and critically governs whether monolayer or multilayer superlattices are formed. More specifically, it is demonstrated that dilution of the nanoparticle dispersion with a similar solvent (but with different vapour pressure) is an expedient handle to control the nature of self-assembly. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Evaporation rate; gold nanoparticles; Nucleation; Self-assembly

Synthesis and in situ observation of 3D super lattices of gold nanoparticles using oil-in-water emulsion - Dutta, Ankur; Chakraborty, Jayanta; Bhagavatula L. V. Prasad; Sahu, Puspanjali (Journal of Colloid and Interface Science, 2014)
In this work oil-in-water emulsion has been successfully used as a confined environment to grow 3D superlattices of gold nanoparticles. The superlattices were grown from 5 nm uniform gold nanoparticles using slow destabilization method. The confined environment was created by forming a stable emulsion where the gold colloid suspended in toluene was used as oil phase. Superlattices were also formed in bulk solution using the same slow destabilization method. A comparative study reveals that compact superlattices form more readily inside the emulsion drops as compared to bulk precipitation. The unstable colloid (in bulk or as emulsion) was aged for various periods at 5 degrees C to form more compact superlattices. The best superlattices with sharp corners are observed when the superlattices are formed inside the emulsion and aged for a month. Two key parameters, the incubation temperature and anti-solvent concentration, are optimized to obtain larger superlattices with sharp features. A new method is also demonstrated for in situ observation of superlattice formation using an optical microscope. 2014 Elsevier Inc. All rights reserved.
Keywords: 3D nanocrystal superlattices; In situ observation of superlattice formation; Monodisperse gold nanoparticles; Nanocrystal superlattices

Time and temperature effects on the digestive ripening of gold nanoparticles: is there a crossover from digestive ripening to ostwald ripening? - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Langmuir, 2014)
The effects of time and temperature on the gold nanoparticle sizes obtained by digestive ripening have been investigated. In digestive ripening, a polydisperse colloid, upon refluxing with a surface-active ligand in a solvent, gets converted to a nearly monodisperse one. In this study, a polydisperse gold nanoparticle system was heated in 4-tert-butyltoluene with hexadecanethiol at different temperatures, viz., 60, 90, 120, 150, and 180 degrees C for different time periods, and the trends in particle size variations were recorded. At lower temperatures such as 60 and 90 degrees C, after the initial narrowing of the size distribution, the particle sizes remain constant even though the refluxing step is continued for 24 h, substantiating the prevalence of the digestive ripening process. However, at elevated temperatures (120, 150, and 180 degrees C) particle sizes grow continuously, indicating a deviation from the digestive ripening behavior to an Ostwald ripening-type phenomenon.

Preparation of Ag(Shell)-Au(Core) nanoparticles by anti-galvanic reactions: are capping agents the ``real heroes'' of reduction? - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2015)
The formation of Ag(shell)-Au(core) nanoparticles by the reduction of Ag+ ions on preformed Au NPs, mediated by the capping agents like dodecylamine is described. We clearly established that while monodisperse Ag(shell)-Au(core) structures can be formed in presence of weak surface binding ligands such as amines, strong binding ligands such as thiols, lead to formation of separate monometallic Au and Ag particles. Apart from highlighting the influence of metal-ligand binding strength on the formation of core-shell nanoparticle architectures, our study also provides an easy means to produce Ag( shell)-Au( core) structures. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ag(shell)-Au(core) nanoparticles; Anti-Galvanic reactions

Digestive ripening of Au nanoparticles by multidentate ligands - Sahu, Puspanjali; Shimpi, Jayesh; Lee, Han Ju; Lee, T. Randall; Prasad, Bhagavatula L. V (Langmuir, 2017)
The efficiency of multidentate ligands as digestive ripening agents for the preparation of monodisperse Au nanoparticles was investigated. This systematic investigation was performed using ligands possessing one, two, or three thiol moieties as ligands/digestive ripening agents. Our results clearly establish that among the different ligands, those that are monodentate and the use of temperatures in the range of 60 °C and 120 °C offer the best conditions for digestive ripening. In addition, when digestive ripening was carried out at lower temperatures (e.g., 60 °C), the nanoparticle size increased as the number of thiol groups per ligand increased. However, in the case of ligands possessing two and three thiol moieties when they are heated with polydispersed particles at higher temperatures (120 °C or 180 °C), the etching process dominates, which affects the quality of the nanoparticles in terms of their monodispersity. We conclude that the temperature-dependent strength of the interaction between the ligand headgroup and the nanoparticle surface plays a vital role in controlling the final particle sizes.